Single-phase (Hf, Ta) (C, N) transition metal carbonitride powder as well as preparation method and application thereof

The preparation of (Hf,Ta)(C,N) micron cube powder under a nitrogen atmosphere through the melting-precipitation-nitriding mechanism has solved the problems of complex preparation process and difficult component control in the prior art, and achieved efficient preparation of materials and performance improvement, suitable for high temperature and high pressure environments.

CN119263840APending Publication Date: 2025-01-07SHANDONG UNIV OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411645863.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

When preparing multi-component transition metal carbon nitrides, the preparation process is complex, the components are difficult to control, and the introduction of oxygen elements is easy to affect the purity and performance, limiting the practical application of materials and large-scale production.

Method used

Using the melt-precipitation-nitriding mechanism, metal cobalt powder is used as flux, and the HfC and TaC powders are heated under a nitrogen atmosphere, and the cobalt-rich alloy matrix is ​​removed through corrosion to prepare (Hf,Ta)(C,N) micrometer cubes Powder, to achieve controllable components and uniform distribution of elements.

Benefits of technology

The preparation process is simplified, equipment requirements and raw material costs are reduced, the mechanical properties and high thermal stability of the materials are improved, and it is suitable for applications in aerospace and nuclear reactors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a method for preparing (Hf, Ta) (C, N) micron cubes. The method is based on a melting-precipitation-nitriding mechanism, hafnium carbide (HfC) and tantalum carbide (TaC) powder are used as raw materials, and metal cobalt powder is used as a flux. The preparation method comprises the following steps: uniformly mixing three powders according to a specific ratio, pre-pressing and molding, transferring into a tubular furnace or a high-temperature furnace, and carrying out normal-pressure high-temperature heat treatment in a nitrogen atmosphere. And the (Hf, Ta) (C, N) micron cube is finally obtained through the steps of removing a cobalt alloy matrix through subsequent acid corrosion, cleaning and drying. The preparation method disclosed by the invention is low in requirement on equipment, simple and convenient to operate and short in period, and the prepared (Hf, Ta) (C, N) solid solution presents a micron cubic morphology, is controllable in components and uniform in element distribution, shows excellent mechanical properties, and is particularly suitable for the fields of nuclear reactor power systems, aero-engines, coatings and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a single-phase (Hf, Ta) (C, N) transition metal carbonitride powder, a preparation method and application thereof, and belongs to the technical field of ceramic powder preparation. Background Art

[0002] IVB and VB transition metal carbides or nitrides, as ultra-high temperature ceramics (UHTCs), have melting points exceeding 3000℃. They have excellent properties such as high strength, high hardness and high thermal stability, and are therefore widely used in space nuclear reactor power systems, aero engines, tool coatings and abrasive materials. Tantalum carbide (TaC), hafnium carbide (HfC), hafnium nitride (HfN) and tantalum nitride (TaN) have been hot topics in the research of ultra-high temperature ceramics in recent years. They all have a NaCl-type face-centered cubic crystal structure with a space group of Fm3m. α=β=γ=90°, and their lattice constants are very close, namely a=0.4450 nm, a=0.4640 nm, a=0.4533nm and a=0.4340 nm, respectively. In these crystal structures, transition metal Ta and Hf atoms are located at the eight vertices and face centers of the unit cell, while C and N atoms occupy the center of each edge and the center of the unit cell. Transition metal carbides and nitrides are valued for their high melting points and hardness. Specifically, HfC, TaC, HfN, and TaN have melting points of 3890°C, 3880°C, 3380°C, and 3017°C, respectively, and hardnesses of 19 GPa, 20 GPa, 18 GPa, and 32 GPa, respectively. These materials also exhibit excellent electrical and thermal conductivity, reaching 20.0 W / m·K, and have a very small thermal expansion coefficient of only 6.6×10 -6 / K, showing good impact properties. In addition, their resistivity is low, 33μΩ·cm, further highlighting the potential of this type of material in high-performance applications. TaC retains some of the advantages of metal Ta, but also has the advantages of ablation resistance, thermal shock resistance and good wear resistance. It is currently widely used in the field of cutting tools and abrasive materials.

[0003] With the continuous advancement of science and technology, especially the rapid development of nuclear reactors and aerospace, the requirements for ultra-high temperature ceramics are increasing day by day. Single-component carbides or nitrides can no longer meet the needs of complex service environments. Researchers have found that by forming a solid solution, that is, increasing the disorder of the structure and the complexity of the composition, and then changing the bonding characteristics, the material properties can be significantly improved. Therefore, this has become a research hotspot in the field of ultra-high temperature ceramics. Considering the Hf atom (r Hf =0.1585 nm) and Ta atoms (r Ta=0.1457nm) is less than 15% different in radius, and the radii of C atoms (0.29nm) and N atoms (0.3nm) are similar. (Hf,Ta)(C,N) can theoretically form an infinite solid solution. However, research on this solid solution is relatively rare, and existing reports mainly focus on (Hf x Ta 1−x )C. For example, Ghaffari et al. in the paper “Diffusion and solid solution formation between the binary carbides of TaC, HfC and ZrC” prepared (HfC) with uniform composition and high density by cold isostatic pressing at 500 MPa and then heating to 2000℃ in a resistance-heated graphite furnace and flowing argon atmosphere. x Ta 1−x )C solid solution, and found that its hardness is higher than that of HfC and TaC. In addition, Cedillos-Barraza et al. prepared three compositions of (HfC) by two-step spark plasma sintering process (SPS, 2100℃ / 20min / 55MPa and 2350℃ / 20min / 38MPa) in the paper "Sintering behavior, solid solution formation and characterisation of TaC, HfC and TaC-HfC fabricated by spark plasmasintering" 1-x Ta x )C solid solutions (x=0.2, 0.5 and 0.8) and single-component TaC and HfC. The XRD results all confirm the formation of solid solutions, and their lattice constants are between the constituent carbides TaC and HfC, which conforms to Vegard's law. x Hf 1-x The mechanical properties of the solid solution of (Hf)C show that the solid solution hardness exceeds that of the single-component carbides HfC and TaC, especially in the case of equimolar ratios of (Hf 0.5 Ta 0.5 )C sample, the hardness reaches the highest value. On the other hand, (Ta x Hf 1-xThe oxidation resistance of tantalum carbide-hafnium carbidesolid solutions from roomtemperature to 1400℃ was also significantly improved, extending the service life of the material in high-temperature oxidation environments. In the paper "Thermal analysis of tantalum carbide-hafnium carbidesolid solutions from roomtemperature to 1400℃", Zhang et al. systematically studied the oxidation behavior of (Hf,Ta)C with different TaC contents (0, 20, 50, 80 and 100 vol.%) from room temperature to 1400℃ by thermogravimetric analysis-differential scanning calorimetry (TG-DSC) technology. Compared with single-component TaC (750℃) and HfC (800℃), their oxidation resistance was enhanced, especially (Hf,Ta)C with equal volume ratio showed the best performance, with its oxidation starting temperature increased to 940℃ and the oxidation conversion rate at 1400℃ being only 60%. This improved oxidation resistance is mainly attributed to the uniform distribution of Ta and Hf atoms in the solid solution lattice, a structural feature that promotes the formation of high-melting-point Hf-Ta-O oxides during the oxidation process. The formation of this oxide not only effectively inhibits the formation of Ta2O5, which has a large volume mismatch with the carbide, thereby effectively avoiding the spalling of the oxide layer, but also reduces the yield of gaseous products. In addition, the dense oxide layer formed during the oxidation process provides good protection for the carbide substrate material. In subsequent ablation experiments, the (Hf,Ta)C solid solution was exposed to a plasma torch at approximately 2800°C with a gas flow rate reaching the speed of sound (>300m / s) for 60 seconds, 180 seconds, and 300 seconds, respectively. Compared with single-component HfC and TaC, the ablation resistance of the solid solution is significantly improved. Even under extreme conditions, when the ablation lasted for 300 seconds, the (Ta, Hf)C with equal volume ratio also showed the best performance, and the thickness of its dense oxide layer was only 28 microns, which is equivalent to 1 / 10 and 1 / 6 of the thickness of pure TaC and HfC oxide layers. The above results highlight the excellent performance of (Hf, Ta)C solid solution under extreme high temperature conditions, especially its potential application value in aerospace and other fields.

[0004] Furthermore, by partially replacing the carbon atoms in the carbides of multi-metal components with nitrogen atoms, the formation of carbonitrides will lead to changes in the electronic structure of the compound, thereby significantly improving the physical and chemical properties of the material, such as hardness and thermal stability. It provides new possibilities for the development of ultra-high temperature structural ceramics and other high-performance materials. Wang Y et al. successfully synthesized (HfZrTaNbTi)(CN) powder through high-energy ball milling and subsequent heat treatment process (1600℃ / 2h) in the paper "Synthesis, microstructure, and mechanical properties of novel highentropy carbonitrides". And further prepared (HfZrTaNbTi) with a density of 95% by hot pressing technology (1800℃ / 30MPa). 0.2 Zr 0.2 Ta 0.2 Nb 0.2 Ti 0.2 )(C 0.5 N 0.5 ) ceramics. This sample exhibits higher hardness and Young's modulus than the corresponding multi-component transition metal carbides and nitrides; and its thermal conductivity in the range of 300K to 800K is lower than the linear combination of the corresponding carbides and nitrides, which indicates that it has excellent thermal stability and deformation resistance in high-temperature applications. In the subsequent work "Improved oxidation resistance of (ZrNbHfTa)(C,N) high entropycarbonitrides", the researcher successfully prepared (Zr 0.25 Nb 0.25 Hf 0.25 Ta 0.25 )C x N 1-x , x = (1.0, 0.9, 0.8, 0.7), and exhibited excellent oxidation resistance and thermal stability under extreme conditions. Especially when the C / N molar ratio was 7:3, the oxidation onset temperature was the highest, and no cracks appeared in the oxidation product, maintaining structural integrity. Therefore, through careful material design, the preparation of multi-component transition metal carbonitrides, such as (Hf, Ta) (C, N), can significantly improve the comprehensive performance of the material, making it a great potential for application in aerospace, nuclear energy, and other advanced technology fields requiring high temperature stability and oxidation resistance.

[0005] At present, there are three main methods for preparing multi-component transition metal carbonitrides: (1) Solid-phase sintering process: single-component transition metal carbides and transition metal nitrides are used as raw materials. Using solid-phase sintering, these raw materials react at high temperature to form multi-component transition metal carbonitrides. Due to strong covalent bonds and low diffusion coefficients, the preparation process is complex and the synthesis conditions are harsh. It often requires a high temperature and high pressure environment. The slow diffusion affects the uniformity of the composition and increases the grain size, which is not conducive to the optimization of material properties. These challenges not only make it difficult to accurately control the composition, but also limit the actual production application and large-scale production of the material because the operation and maintenance costs of special equipment are high. (2) Carbothermal reduction-nitridation reaction: single-component transition metal oxides and carbon are used as raw materials and subjected to high-temperature heat treatment in a nitrogen atmosphere. This process first reduces the oxide to metal through a carbothermal reduction reaction, and then undergoes a nitridation reaction under the action of nitrogen to form carbonitrides. (3) High-temperature heat treatment-nitridation process: using transition metals and carbon as raw materials, powders are prepared through a high-temperature heat treatment-nitridation process. The second and third methods are very sensitive to oxygen and are prone to introducing oxygen into the solid solution during the preparation process, affecting the purity and performance of the final product. To overcome these obstacles, the present invention uses a melting-precipitation-nitridation mechanism, single-component transition metal carbides as raw materials (HfC and TaC), and metal cobalt powder as flux to explore a new technology for synthesizing (Hf, Ta) (C, N) under normal pressure in a nitrogen atmosphere to achieve better composition control, reduce grain growth and improve production efficiency. It aims to develop new high-performance materials that can meet performance requirements and are suitable for large-scale production, and expand their application prospects in aerospace, nuclear energy and other high-tech fields. Summary of the invention

[0006] The present invention provides a method for preparing (Hf x Ta 1-x A new process for preparing microcubes of (CN) micrometers; using metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, the specific preparation steps include: (1) weighing hafnium carbide (HfC) powder and tantalum carbide (TaC) powder in a molar ratio of 1:(0.11-9) respectively and mixing them evenly; (2) weighing cobalt powder in a mass ratio of carbide to metal cobalt powder of 1:(1-5), and mixing it evenly with the powder obtained in step (1). (3) Pressing the mixed powder obtained in step (2) into a tablet, placing it in a tube furnace or a high-temperature furnace, and performing heat treatment in a nitrogen atmosphere, heating it to 1500-1900°C at a heating rate of 2-5°C / min, keeping it at that temperature for 0.5-10 hours, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal block; (4) Soaking the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining (Hf x Ta 1-x)(CN) powder, and repeatedly wash it with deionized water to remove impurities and ions on the powder surface. (5) Place the cleaned powder in an oven and dry it at 50~80℃ to finally obtain (Hf x Ta 1-x )(CN) micron cubic powder.

[0007] The preparation method of the present invention has low requirements on equipment, easy to obtain raw materials, simple preparation steps and short preparation cycle; the prepared (Hf x Ta 1-x )(CN)The solid solution composition is controllable and the elements are evenly distributed, showing excellent mechanical properties and high thermal stability, and is suitable for use in nuclear reactor power systems, aerospace engines, tool coatings, and abrasive materials. This provides a new and efficient solid solution preparation solution for related technical fields. Principle of the Invention

[0008] The present invention is based on the melting-precipitation-nitridation mechanism and creates a new method for preparing (Hf x Ta 1-x )(CN) microcubes. This process is divided into two main stages:

[0009] (I) Melting process: Cobalt powder is used as flux, and the heat treatment temperature is higher than the melting point of metallic cobalt. In this process, the molten cobalt wets the TaC and HfC particles, promotes the decomposition of carbides and forms a ternary (Co-Hf-Ta) molten alloy and solid carbon. The reaction equation is as follows: m ·HfC (s) + n ·TaC (s) +(1- m - n )·Co (l) →Co (1-m-n) -Hf m -Ta n(l) +( m + n )·C (s) (1)

[0010] in, m and n Respectively represent the molar percentage of Hf and Ta in the generated cobalt-based alloy (0≤ m ≤1, 0≤ n ≤1); l and s Represents liquid and solid respectively.

[0011] (II) Precipitation-nitridation process: When the content of Hf and Ta in the Co-Hf-Ta alloy reaches the upper limit, these metal components will precipitate from the molten alloy and react with carbon and nitrogen to form a (Hf, Ta) (C, N) solid solution. This reaction can be expressed as: Co (1-m-n) -Hf m -Ta n(l) + x ( m+n )C (s) +1 / 2( m+n )(1-x)N 2(g) →( m+n )(Hf m / (m+n) Ta n / (m+n) )(C x N 1-x ) (s) +(1- mn )Co (l) (2)

[0012] The introduction of Co flux not only changed the material transport mechanism of carbides from the original slower solid-phase diffusion to faster molten Co-Hf-Ta alloy flow, but also accelerated the migration rate of the various components of the carbide, thereby successfully preparing the (Hf, Ta) (C, N) solid solution under normal pressure nitrogen atmosphere.

[0013] The present invention has the following advantages:

[0014] (1) The preparation method of hafnium tantalum carbon nitrogen solid solution (Hf, Ta) (C, N) provided by the present invention can successfully prepare the solid solution. The preparation process has the advantages of simple operation steps, safety and reliability, and energy saving.

[0015] (2) The hafnium tantalum carbon nitrogen solid solution micron powder prepared by the present invention presents a cubic block morphology, and has the characteristics of controllable composition and uniform element distribution.

[0016] (3) (Hf, Ta) (C, N) solid solution powder has high hardness, good chemical stability, excellent oxidation resistance, high temperature and chemical corrosion resistance, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is the (Hf prepared in Example 1 0.1 Ta 0.9 )(C 0.76 N 0.24 )XRD pattern of the powder.

[0018] Figure 2 is the (Hf prepared in Example 1 0.1 Ta 0.9)(C 0.76 N 0.24 )SEM image of the powder.

[0019] Figure 3 is the (Hf prepared in Example 1 0.1 Ta 0.9 )(C 0.76 N 0.24 ) Particle size distribution diagram of powder.

[0020] Figure 4 is the (Hf prepared in Example 2 0.2 Ta 0.8 )(C 0.76 N 0.24 )XRD pattern of the powder.

[0021] Figure 5 is the (Hf prepared in Example 2 0.2 Ta 0.8 )(C 0.76 N 0.24 )SEM image of the powder.

[0022] Figure 6 is the (Hf prepared in Example 2 0.2 Ta 0.8 )(C 0.76 N 0.24 ) Particle size distribution diagram of powder.

[0023] Figure 7 is prepared in Example 3 (Hf 0.3 Ta 0.7 )(C 0.76 N 0.24 )XRD pattern of the powder.

[0024] Figure 8 is prepared in Example 3 (Hf 0.3 Ta 0.7 )(C 0.76 N 0.24 )SEM image of the powder.

[0025] Fig. 9 is prepared in Example 3 (Hf 0.3 Ta 0.7 )(C 0.76 N 0.24 ) Particle size distribution of powder Fig.10 is the (Hf prepared in Example 4 0.4 Ta 0.6 )(C 0.76 N 0.24 )XRD pattern of the powder.

[0026] Fig.11 is the (Hf prepared in Example 4 0.4 Ta 0.6 )(C 0.76 N 0.24 )SEM image of the powder.

[0027] Fig.12 is the (Hf prepared in Example 4 0.4 Ta 0.6 )(C 0.76 N 0.24 ) Particle size distribution diagram of powder.

[0028] Fig.13 is the (Hf prepared in Example 4 0.4 Ta 0.6 )(C 0.76 N 0.24 )EDS spectrum of the powder.

[0029] Fig.14 is prepared in Example 5 (Hf 0.5 Ta 0.5 )(C 0.76 N 0.24 )XRD pattern of the powder.

[0030] Fig.15 is prepared in Example 5 (Hf 0.5 Ta 0.5 )(C 0.76 N 0.24 )SEM image of the powder.

[0031] Fig.16 is prepared in Example 5 (Hf 0.5 Ta 0.5 )(C 0.76 N 0.24 ) Particle size distribution diagram of powder.

[0032] Fig.17 is prepared in Example 5 (Hf 0.5 Ta 0.5 )(C 0.76 N 0.24 )EDS spectrum of the powder.

[0033] Fig.18 is prepared in Example 6 (Hf 0.6 Ta 0.4 )(C 0.76 N 0.24 )XRD pattern of the powder.

[0034] Fig.19 is prepared in Example 6 (Hf0.6 Ta 0.4 )(C 0.76 N 0.24 )SEM image of the powder.

[0035] Fig. 20 is prepared in Example 6 (Hf 0.6 Ta 0.4 )(C 0.76 N 0.24 ) Particle size distribution of powder Fig.21 is prepared in Example 6 (Hf 0.6 Ta 0.4 )(C 0.76 N 0.24 )EDS spectrum of the powder.

[0036] Fig. 22 is prepared in Example 7 (Hf 0.7 Ta 0.3 )(C 0.76 N 0.24 )XRD pattern of the powder.

[0037] Fig.23 is prepared in Example 7 (Hf 0.7 Ta 0.3 )(C 0.76 N 0.24 )SEM image of the powder.

[0038] Fig.24 is prepared in Example 7 (Hf 0.7 Ta 0.3 )(C 0.76 N 0.24 ) Particle size distribution diagram of powder.

[0039] Fig.25 is prepared in Example 8 (Hf 0.8 Ta 0.2 )(C 0.76 N 0.24 )XRD pattern of the powder.

[0040] Fig.26 is prepared in Example 8 (Hf 0.8 Ta 0.2 )(C 0.76 N 0.24 )SEM image of the powder.

[0041] Fig. 27 is prepared in Example 8 (Hf 0.8 Ta 0.2 )(C 0.76 N 0.24) Particle size distribution diagram of powder.

[0042] Fig.28 is prepared in Example 8 (Hf 0.8 Ta 0.2 )(C 0.76 N 0.24 )EDS spectrum of the powder.

[0043] Fig.29 is prepared in Example 9 (Hf 0.9 Ta 0.1 )(C 0.76 N 0.24 )XRD pattern of the powder.

[0044] Fig.30 is prepared in Example 9 (Hf 0.9 Ta 0.1 )(C 0.76 N 0.24 )SEM image of the powder.

[0045] Fig.31 is prepared in Example 9 (Hf 0.9 Ta 0.1 )(C 0.76 N 0.24 ) Particle size distribution diagram of powder.

[0046] Fig.32 is the (Hf prepared in Example 10 0.2 Ta 0.8 )(C 0.81 N 0.19 )XRD pattern of the powder.

[0047] Fig.33 is the (Hf prepared in Example 10 0.2 Ta 0.8 )(C 0.81 N 0.19 )SEM image of the powder.

[0048] Fig.34 is the (Hf prepared in Example 10 0.2 Ta 0.8 )(C 0.81 N 0.19 ) Particle size distribution diagram of powder.

[0049] Fig.35 is the (Hf prepared in Example 10 0.2 Ta 0.8 )(C 0.81 N 0.19 )EDS spectrum of the powder.

[0050] Fig.36 is the (Hf prepared in Example 11 0.4 Ta 0.6 )(C 0.81 N 0.19 )XRD pattern of the powder.

[0051] Fig.37 is the (Hf prepared in Example 11 0.4 Ta 0.6 )(C 0.81 N 0.19 )SEM image of the powder.

[0052] Fig.38 is the (Hf prepared in Example 11 0.4 Ta 0.6 )(C 0.81 N 0.19 ) Particle size distribution diagram of powder.

[0053] Fig.39 is the (Hf prepared in Example 12 0.5 Ta 0.5 )(C 0.81 N 0.19 )XRD pattern of the powder.

[0054] Fig.40 is the (Hf prepared in Example 12 0.5 Ta 0.5 )(C 0.81 N 0.19 )SEM image of the powder.

[0055] Fig.41 is the (Hf prepared in Example 12 0.5 Ta 0.5 )(C 0.81 N 0.19 ) Particle size distribution diagram of powder.

[0056] Fig.42 is the (Hf prepared in Example 12 0.5 Ta 0.5 )(C 0.81 N 0.19 )EDS spectrum of the powder.

[0057] Fig.43 is the (Hf prepared in Example 13 0.6 Ta 0.4 )(C 0.81 N 0.19 )XRD pattern of the powder.

[0058] Fig.44 is the (Hf prepared in Example 130.6 Ta 0.4 )(C 0.81 N 0.19 )SEM image of the powder.

[0059] Fig.45 is the (Hf prepared in Example 13 0.6 Ta 0.4 )(C 0.81 N 0.19 ) Particle size distribution diagram of powder.

[0060] Fig.46 is the (Hf prepared in Example 13 0.6 Ta 0.4 )(C 0.81 N 0.19 )EDS spectrum of the powder.

[0061] Fig.47 is the (Hf prepared in Example 14 0.8 Ta 0.2 )(C 0.81 N 0.19 )XRD pattern of the powder.

[0062] Fig.48 is the (Hf prepared in Example 14 0.8 Ta 0.2 )(C 0.81 N 0.19 )SEM image of the powder.

[0063] Fig.49 is the (Hf prepared in Example 14 0.8 Ta 0.2 )(C 0.81 N 0.19 ) Particle size distribution diagram of powder.

[0064] Fig.50 is the (Hf prepared in Example 14 0.8 Ta 0.2 )(C 0.81 N 0.19 )EDS spectrum of the powder.

[0065] Fig.51 is the hardness of the prepared (Hf,Ta)(C,N) powder.

[0066] Fig.52 is the (Hf prepared in Example 15 0.2 Ta 0.8 )(C 0.89 N 0.11 )XRD pattern of the powder.

[0067] Fig.53 is the (Hf prepared in Example 15 0.2 Ta 0.8 )(C 0.89 N 0.11 )SEM image of the powder.

[0068] Fig.54 is the (Hf prepared in Example 15 0.2 Ta 0.8 )(C 0.89 N 0.11 ) Particle size distribution diagram of powder.

[0069] Fig.55 is the (Hf prepared in Example 15 0.2 Ta 0.8 )(C 0.89 N 0.11 )EDS spectrum of the powder.

[0070] Fig.56 is the (Hf prepared in Example 16 0.4 Ta 0.6 )(C 0.89 N 0.11 )XRD pattern of the powder.

[0071] Fig.57 is the (Hf prepared in Example 16 0.4 Ta 0.6 )(C 0.89 N 0.11 )SEM image of the powder.

[0072] Fig.58 is the (Hf prepared in Example 16 0.4 Ta 0.6 )(C 0.89 N 0.11 ) Particle size distribution diagram of powder.

[0073] Fig.59 is the (Hf prepared in Example 16 0.4 Ta 0.6 )(C 0.89 N 0.11 )EDS spectrum of the powder.

[0074] Fig.60 is prepared in Example 17 (Hf 0.5 Ta 0.5 )(C 0.89 N 0.11 )XRD pattern of the powder.

[0075] Fig.61 is prepared in Example 17 (Hf0.5 Ta 0.5 )(C 0.89 N 0.11 )SEM image of the powder.

[0076] Fig.62 is prepared in Example 17 (Hf 0.5 Ta 0.5 )(C 0.89 N 0.11 ) Particle size distribution diagram of powder.

[0077] Fig.63 is prepared in Example 17 (Hf 0.5 Ta 0.5 )(C 0.89 N 0.11 )EDS spectrum of the powder.

[0078] Fig.64 is the (Hf prepared in Example 18 0.6 Ta 0.4 )(C 0.89 N 0.11 )XRD pattern of the powder.

[0079] Fig.65 is the (Hf prepared in Example 18 0.6 Ta 0.4 )(C 0.89 N 0.11 )SEM image of the powder.

[0080] Fig.66 is the (Hf prepared in Example 18 0.6 Ta 0.4 )(C 0.89 N 0.11 ) Particle size distribution diagram of powder.

[0081] Fig.67 is the (Hf prepared in Example 18 0.6 Ta 0.4 )(C 0.89 N 0.11 )EDS spectrum of the powder.

[0082] Fig.68 is prepared in Example 19 (Hf 0.8 Ta 0.2 )(C 0.89 N 0.11 )XRD pattern of the powder.

[0083] Fig.69 is prepared in Example 19 (Hf 0.8 Ta 0.2 )(C0.89 N 0.11 )SEM image of the powder.

[0084] Fig.70 is prepared in Example 19 (Hf 0.8 Ta 0.2 )(C 0.89 N 0.11 ) Particle size distribution diagram of powder.

[0085] Fig.71 is prepared in Example 19 (Hf 0.8 Ta 0.2 )(C 0.89 N 0.11 )EDS spectrum of the powder. DETAILED DESCRIPTION

[0087] The technical solution of the present invention is not limited to the specific embodiments listed below, but also includes any combination of the specific implementation modes.

[0088] 1. Preparation of (Hf,Ta)(C,N) powder

[0089] Example 1

[0090] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weigh hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:9 respectively and mix them evenly; (2) weigh cobalt powder in a mass ratio of 3:7 and mix it evenly with the powder obtained in step (1); (3) press the mixed powder obtained in step (2) into a prefabricated block and then transfer it to a tube furnace for heat treatment in a nitrogen atmosphere, heating to 1500°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, and then cooling to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immerse the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, then filter the remaining powder, and repeatedly wash it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.1 Ta 0.9 )(C 0.76 N 0.24 ) micron powder.

[0091] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Figure 1As shown. In the 2θ range of 30° to 80°, five obvious XRD diffraction peaks were detected, corresponding to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.1 Ta 0.9 )(C 0.76 N 0.24 ) has a lattice constant of 4.4564 Å. This value is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0092] Figure 2 Scanning electron microscopy (SEM) showed that (Hf 0.1 Ta 0.9 )(C 0.76 N 0.24 )Microstructure of solid solution powder. Figure 2 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Figure 2 (b) reveals that the side lengths of these cuboids are between 2 and 6 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1500℃, the solid solution particle morphology formed is transformed into a regular cuboid morphology. Figure 3 The particle size distribution is shown. The distribution is somewhat skewed, mainly concentrated in 2 to 3 microns, accounting for more than 30%. The average particle size is 2.82 microns.

[0093] Example 2

[0094] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:4 respectively and mixing them evenly; (2) weighing cobalt powder in a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a tubular furnace for heat treatment in a nitrogen atmosphere, heating to 1500°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.2 Ta 0.8 )(C 0.76N 0.24 ) micron powder.

[0095] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Figure 4 As shown. In the 2θ range of 30° to 80°, five obvious XRD diffraction peaks were detected, corresponding to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.2 Ta 0.8 )(C 0.76 N 0.24 ) has a lattice constant of 4.4632 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0096] Figure 5 Scanning electron microscopy (SEM) showed that (Hf 0.2 Ta 0.8 )(C 0.76 N 0.24 )Microstructure of solid solution powder. Figure 5 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Figure 5 (b) reveals that the side lengths of these cuboids are between 1 and 3 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1500℃, the solid solution particle morphology formed is transformed into a regular cuboid morphology. Figure 6 The particle size distribution is shown. The distribution is somewhat skewed, mainly concentrated in 1 to 2 microns, accounting for more than 35%. The average particle size is 1.51 microns. Example 3

[0097] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:2.33 respectively and mixing them evenly; (2) weighing cobalt powder in a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a tubular furnace for heat treatment in a nitrogen atmosphere, heating to 1500°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.3 Ta 0.7 )(C 0.76 N 0.24 ) micron powder.

[0098] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Figure 7 As shown. In the 2θ range of 30° to 80°, five obvious XRD diffraction peaks were detected, corresponding to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.3 Ta 0.7 )(C 0.76 N 0.24 ) has a lattice constant of 4.4740 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0099] Figure 8 Scanning electron microscopy (SEM) showed that (Hf 0.3 Ta 0.7 )(C 0.76 N 0.24 )Microstructure of solid solution powder. Figure 8 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Figure 8 (b) reveals that the side lengths of these cuboids are between 1 and 5 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1500℃, the solid solution particle morphology formed is transformed into a regular cuboid morphology. Fig. 9The particle size distribution is shown. The distribution is somewhat skewed, mainly concentrated in 1 to 2 microns, accounting for more than 40%. The average particle size is 1.17 microns. Example 4

[0100] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:1.5 respectively and mixing them evenly; (2) weighing cobalt powder at a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a tubular furnace for heat treatment in a nitrogen and oxygen-free atmosphere, heating to 1500°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.4 Ta 0.6 )(C 0.76 N 0.24 ) micron powder.

[0101] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.10 As shown. In the 2θ range 30 o Up to 80 o The five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.4 Ta 0.6 )(C 0.76 N 0.24 ) has a lattice constant of 4.4953 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0102] Fig.11 Scanning electron microscopy (SEM) showed that (Hf 0.4 Ta 0.6 )(C 0.76 N 0.24 )Microstructure of solid solution powder. Fig.11 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.11 (b) reveals that the side length of most cuboid particles is between 1 and 3 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1500℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.12 The particle size distribution is shown; it shows a normal distribution trend, with the distribution mainly concentrated at 2 microns, accounting for more than 35%. The average particle size is 1.42 microns.

[0103] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.13 As shown. The analysis results show that these particles contain four elements: Hf, Ta, C and N. Among them, the molar ratio of Hf to Ta is 1:1.58, which is consistent with the pre-designed ratio. The above data can confirm the successful preparation of (Hf 0.4 Ta 0.6 )(C 0.76 N 0.24 ) solid solution. Example 5

[0104] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weigh hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:1 respectively and mix them evenly; (2) weigh cobalt powder in a mass ratio of 3:7 and mix it evenly with the powder obtained in step (1); (3) press the mixed powder obtained in step (2) into a prefabricated block and then transfer it to a tube furnace for heat treatment in a nitrogen atmosphere, heating to 1500°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, and then cooling to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immerse the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, then filter the remaining powder, and repeatedly wash it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.5 Ta 0.5 )(C 0.76 N 0.24 ) micron powder.

[0105] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.14 As shown. In the 2θ range 30 o Up to 80 oThe five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.5 Ta 0.5 )(C 0.76 N 0.24 ) has a lattice constant of 4.5203 ​​Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.460 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0106] Fig.15 Scanning electron microscopy (SEM) showed that (Hf 0.5 Ta 0.5 )(C 0.76 N 0.24 )Microstructure of solid solution powder. Fig.15 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.15 (b) reveals that the side length of most cuboid particles is between 1 and 2 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1500℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.16 The particle size distribution is shown; it shows a normal distribution trend, with the distribution mainly concentrated between 1 and 2 microns, accounting for more than 40%. The average particle size is 1.31 microns.

[0107] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.17 As shown. The analysis results show that these particles contain four elements: Hf, Ta, C and N. Among them, the molar ratio of Hf to Ta is 1:0.98, which is consistent with the pre-designed ratio. The above data can confirm the successful preparation of (Hf 0.5 Ta 0.5 )(C 0.76 N 0.24 ) solid solution.

[0108] Example 6

[0109] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:0.67 respectively and mixing them evenly; (2) weighing cobalt powder at a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a tubular furnace for heat treatment in a nitrogen atmosphere, heating to 1500°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.6 Ta 0.4 )(C 0.76 N 0.24 ) micron powder.

[0110] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.18 As shown. In the 2θ range 30 o Up to 80 o The five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.6 Ta 0.4 )(C 0.76 N 0.24 ) has a lattice constant of 4.5378 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0111] Fig.19 Scanning electron microscopy (SEM) showed that (Hf 0.6 Ta 0.4 )(C 0.76 N 0.24 )Microstructure of solid solution powder. Fig.19 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.19(b) reveals that the side length of most cuboid particles is between 1 and 3 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1500℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig. 20 The particle size distribution is shown; it shows a skewed distribution trend, with the distribution mainly concentrated between 1 and 2 microns, accounting for more than 25%. The average particle size is 1.43 microns.

[0112] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.21 The analysis results show that these particles contain four elements: Hf, Ta, C and N. Among them, the molar ratio of Hf to Ta is 1:0.64, which is consistent with the pre-designed ratio, thus confirming the successful preparation of (Hf 0.6 Ta 0.4 )(C 0.76 N 0.24 ) solid solution. Example 7

[0113] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:0.43 respectively and mixing them evenly; (2) weighing cobalt powder at a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a tubular furnace for heat treatment in a nitrogen atmosphere, heating to 1500°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.7 Ta 0.3 )(C 0.76 N 0.24 ) micron powder.

[0114] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig. 22 Shown: In the 2θ range 30 o Up to 80 oThe five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.7 Ta 0.3 )(C 0.76 N 0.24 ) has a lattice constant of 4.5543 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0115] Fig.23 Scanning electron microscopy (SEM) showed that (Hf 0.7 Ta 0.3 )(C 0.76 N 0.24 )Microstructure of solid solution powder. Fig.23 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.23 (b) reveals that the side length of most cuboid particles is between 0 and 2 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1500℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.24 The particle size distribution is shown; it shows a normal distribution trend, with the distribution mainly concentrated between 1 and 2 microns, accounting for more than 45%. The average particle size is 1.26 microns. Example 8

[0116] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:0.25 respectively and mixing them evenly; (2) weighing cobalt powder at a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a tubular furnace for heat treatment in a nitrogen atmosphere, heating to 1500°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.8 Ta 0.2 )(C 0.76 N 0.24) micron powder.

[0117] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.25 Shown: In the 2θ range 30 o Up to 80 o The five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.8 Ta 0.2 )(C 0.76 N 0.24 ) has a lattice constant of 4.5661 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0118] Fig.26 Scanning electron microscopy (SEM) showed that (Hf 0.8 Ta 0.2 )(C 0.76 N 0.24 )Microstructure of solid solution powder. Fig.26 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.26 (b) reveals that the side length of most cuboid particles is between 1 and 2 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1500℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig. 27 The particle size distribution is shown; it shows a normal distribution trend, with the distribution mainly concentrated between 1 and 2 microns, accounting for more than 30%. The average particle size is 1.44 microns.

[0119] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.29 The analysis results show that these particles contain four elements: Hf, Ta, C and N. The molar ratio of Hf to Ta is 1:0.25, which is consistent with the pre-designed ratio, thus confirming the successful preparation of (Hf 0.8 Ta 0.2 )(C 0.76 N 0.24 ) solid solution. Example 9

[0120] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:0.11 respectively and mixing them evenly; (2) weighing cobalt powder in a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a tubular furnace for heat treatment in a nitrogen atmosphere, heating to 1500°C at a heating rate of 5°C / min, keeping the temperature for 10 hours, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.9 Ta 0.1 )(C 0.76 N 0.24 ) micron powder.

[0121] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.29 Shown: In the 2θ range 30 o Up to 80 o The five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.9 Ta 0.1 )(C 0.76 N 0.24 ) has a lattice constant of 4.5799 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0122] Fig.30 Scanning electron microscopy (SEM) showed that (Hf 0.9 Ta 0.1 )(C 0.76 N 0.24 )Microstructure of solid solution powder. Fig.30 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.30(b) reveals that the side length of most cuboid particles is between 0 and 2 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1500℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.31 The particle size distribution is shown; it shows a normal distribution trend, with the distribution mainly concentrated between 0 and 2 microns, accounting for more than 30%. The average particle size is 1.38 microns. Example 10

[0123] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weigh hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:4 respectively and mix them evenly; (2) weigh cobalt powder in a mass ratio of 3:7 and mix it evenly with the powder obtained in step (1); (3) press the mixed powder obtained in step (2) into a prefabricated block and then transfer it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating to 1700°C at a heating rate of 2°C / min, keeping the temperature for 1h, and then cooling to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immerse the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, then filter the remaining powder, and repeatedly wash it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.2 Ta 0.8 )(C 0.81 N 0.19 ) micron powder.

[0124] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.32 Shown: In the 2θ range 30 o Up to 80 o The five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.2 Ta 0.8 )(C 0.81 N 0.19 ) is 4.4755 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0125] Fig.33Scanning electron microscopy (SEM) showed that (Hf 0.2 Ta 0.8 )(C 0.81 N 0.19 )Microstructure of solid solution powder. Fig.33 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.33 (b) reveals that the side lengths of most cuboid particles are between 1 and 9 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1700℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.34 The particle size distribution is shown; it shows a normal distribution trend, with the distribution peak mainly concentrated between 2.5 and 3 microns, accounting for about 20%. The average particle size is 2.97 microns.

[0126] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.35 The analysis results show that these particles contain four elements: Hf, Ta, C and N. Among them, the molar ratio of Hf to Ta is 1:4.20, which is consistent with the pre-designed ratio, thus confirming the successful preparation of (Hf 0.2 Ta 0.8 )(C 0.81 N 0.19 ) solid solution.

[0127] Embodiment 11

[0128] Using metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, the specific steps are as follows: (1) weigh hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:1.5 respectively and mix them evenly; (2) weigh cobalt powder at a mass ratio of 3:7 between carbide and cobalt powder, and mix them evenly with the powder obtained in step (1); (3) press the mixed powder obtained in step (2) into a prefabricated block and transfer it to a high-temperature furnace for heat treatment under a nitrogen atmosphere, heating to 1700°C at a heating rate of 2°C / min, keeping the temperature for 1h, soaking in nitric acid solution, dissolving the cobalt-rich alloy matrix through corrosion, and then filtering the remaining powder, and repeatedly washing with deionized water to remove impurities and ions on the surface of the powder. (5) Place the cleaned powder in an oven and dry it at 60°C to finally obtain (Hf 0.4 Ta 0.6 )(C 0.81 N 0.19 ) micron powder.

[0129] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.36 Shown: In the 2θ range 30 o Up to 80 o The five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.4 Ta 0.6 )(C 0.81 N 0.19 ) has a lattice constant of 4.5003 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0130] Fig.37 Scanning electron microscopy (SEM) showed that (Hf 0.4 Ta 0.6 )(C 0.81 N 0.19 )Microstructure of solid solution powder. Fig.37 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.37 (b) reveals that the side length of most cuboid particles is between 1 and 3 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1700℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.38 The particle size distribution is shown; it shows a skewed distribution trend, with the distribution peak mainly concentrated between 1 and 2 microns, accounting for more than 40%. The average particle size is 1.25 microns. Example 12

[0131] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:1 respectively and mixing them evenly; (2) weighing cobalt powder in a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating it to 1700°C at a heating rate of 2°C / min, keeping it at that temperature for 1h, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.5 Ta 0.5 )(C 0.81 N 0.19 ) micron powder.

[0132] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.39 Shown: In the 2θ range 30 o Up to 80 o The five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.5 Ta 0.5 )(C 0.81 N 0.19 ) is 4.5267 Å, ​​which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0133] Fig.40 Scanning electron microscopy (SEM) showed that (Hf 0.5 Ta 0.5 )(C 0.81 N 0.19 )Microstructure of solid solution powder. Fig.40 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.40(b) reveals that the side length of most cuboid particles is between 1 and 4 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1700℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.41 The particle size distribution is shown; it shows a skewed distribution trend, with the distribution peak mainly concentrated between 1 and 2 microns, accounting for about 40%. The average particle size is 1.46 microns.

[0134] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.42 The analysis results show that these particles contain four elements: Hf, Ta, C and N. The molar ratio of Hf to Ta is 1:1, which is consistent with the pre-designed ratio, thus confirming the successful preparation of (Hf 0.5 Ta 0.5 )(C 0.81 N 0.19 ) solid solution. Embodiment 13

[0135] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:0.67 respectively and mixing them evenly; (2) weighing cobalt powder at a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating it to 1700°C at a heating rate of 2°C / min, keeping it at that temperature for 1h, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.6 Ta 0.4 )(C 0.81 N 0.19 ) micron powder.

[0136] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.43 Shown: In the 2θ range 30 o Up to 80 oThe five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.6 Ta 0.4 )(C 0.81 N 0.19 ) has a lattice constant of 4.5414 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0137] Fig.44 Scanning electron microscopy (SEM) showed that (Hf 0.6 Ta 0.4 )(C 0.81 N 0.19 )Microstructure of solid solution powder. Fig.44 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.44 (b) reveals that the side length of most cuboid particles is between 1 and 4 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1700℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.45 The particle size distribution is shown; it shows a normal distribution trend, with the distribution peak mainly concentrated between 1 and 2 microns, accounting for about 25%. The average particle size is 1.75 microns.

[0138] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.46 The analysis results show that these particles contain four elements: Hf, Ta, C and N. Among them, the molar ratio of Hf to Ta is 1:0.72, which confirms the successful preparation of (Hf 0.6 Ta 0.4 )(C 0.81 N 0.19 ) solid solution. Embodiment 14

[0139] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:0.25 respectively and mixing them evenly; (2) weighing cobalt powder at a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating it to 1700°C at a heating rate of 2°C / min, keeping it at that temperature for 1h, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.8 Ta 0.2 )(C 0.81 N 0.19 ) micron powder.

[0140] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.47 Shown: In the 2θ range 30 o Up to 80 o The five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.8 Ta 0.2 )(C 0.81 N 0.19 ) is 4.5748 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0141] Fig.48 Scanning electron microscopy (SEM) showed that (Hf 0.8 Ta 0.2 )(C 0.81 N 0.19 )Microstructure of solid solution powder. Fig.48 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.48(b) reveals that the side lengths of most cuboid particles are between 0 and 4 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1700℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.49 The particle size distribution is shown; it shows a skewed distribution trend, with the distribution peak mainly concentrated at 2 microns, accounting for about 30%. The average particle size is 1.75 microns.

[0142] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.50 The analysis results show that these particles contain four elements: Hf, Ta, C and N. The molar ratio of Hf to Ta is 1:0.26, which is consistent with the pre-designed ratio, thus confirming the successful preparation of (Hf 0.8 Ta 0.2 )(C 0.81 N 0.19 ) solid solution. Embodiment 15

[0143] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:4 respectively and mixing them evenly; (2) weighing cobalt powder in a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating to 1900°C at a heating rate of 2°C / min, keeping the temperature for 0.5 hour, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.2 Ta 0.8 )(C 0.89 N 0.11 ) micron powder.

[0144] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.52 Shown: In the 2θ range 30 o Up to 80 oThe five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.2 Ta 0.8 )(C 0.81 N 0.19 ) has a lattice constant of 4.4820 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0145] Fig.53 Scanning electron microscopy (SEM) showed that (Hf 0.2 Ta 0.8 )(C 0.89 N 0.11 )Microstructure of solid solution powder. Fig.53 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.53 (b) reveals that the side lengths of most cuboid particles are between 3 and 24 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1900℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.54 The particle size distribution is shown; it shows a skewed distribution trend, with the distribution peak mainly concentrated at 8 microns, accounting for more than 15%. The average particle size is 7.50 microns.

[0146] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.55 The analysis results show that these particles contain four elements: Hf, Ta, C and N. The molar ratio of Hf to Ta is 1:4.62, which is consistent with the pre-designed ratio, thus confirming the successful preparation of (Hf 0.2 Ta 0.8 )(C 0.89 N 0.11 ) solid solution.

[0147] Example 16

[0148] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:1.5 respectively and mixing them evenly; (2) weighing cobalt powder at a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating it to 1900°C at a heating rate of 2°C / min, keeping it at this temperature for 0.5 hour, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.4 Ta 0.6 )(C 0.89 N 0.11 ) micron powder.

[0149] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.56 Shown: In the 2θ range 30 o Up to 80 o The five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.4 Ta 0.6 )(C 0.89 N 0.11 ) has a lattice constant of 4.5216 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0150] Fig.57 Scanning electron microscopy (SEM) showed that (Hf 0.4 Ta 0.6 )(C 0.89 N 0.11 )Microstructure of solid solution powder. Fig.57 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.57(b) reveals that the side lengths of most cuboid particles are between 3 and 15 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1900℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.58 The particle size distribution is shown; it shows a skewed distribution trend, with the distribution peak mainly concentrated at 16 microns, accounting for about 10%. The average particle size is 16.25 microns.

[0151] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.59 As shown. The analysis results show that these particles contain four elements: Hf, Ta, C and N. Among them, the molar ratio of Hf to Ta is 1:1.58, which is consistent with the pre-designed ratio. The above data can confirm the successful preparation of (Hf 0.4 Ta 0.6 )(C 0.89 N 0.11 ) solid solution. Embodiment 17

[0152] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:1 respectively and mixing them evenly; (2) weighing cobalt powder in a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating it to 1900°C at a heating rate of 2°C / min, keeping it at this temperature for 0.5 hour, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.5 Ta 0.5 )(C 0.89 N 0.11 ) micron powder.

[0153] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.60 Shown: In the 2θ range 30 o Up to 80 oThe five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.5 Ta 0.5 )(C 0.89 N 0.11 ) has a lattice constant of 4.5391 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0154] Fig.61 Scanning electron microscopy (SEM) showed that (Hf 0.5 Ta 0.5 )(C 0.89 N 0.11 )Microstructure of solid solution powder. Fig.61 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.61 (b) reveals that the side lengths of most cuboid particles are between 2 and 8 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1900℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.62 The particle size distribution is shown; it shows a skewed distribution trend, with the distribution peak mainly concentrated between 6 and 8 microns, accounting for about 20%. The average particle size is 6.99 microns.

[0155] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.63 As shown. The analysis results show that these particles contain four elements: Hf, Ta, C and N. Among them, the molar ratio of Hf to Ta is 1:0.93, which is consistent with the pre-designed ratio. The above data can confirm the successful preparation of (Hf 0.5 Ta 0.5 )(C 0.89 N 0.11 ) solid solution. Embodiment 18

[0156] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:0.67 respectively and mixing them evenly; (2) weighing cobalt powder at a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating to 1900°C at a heating rate of 2°C / min, keeping the temperature for 0.5 hour, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.6 Ta 0.4 )(C 0.89 N 0.11 ) micron powder.

[0157] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.64 Shown: In the 2θ range 30 o Up to 80 o The five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.6 Ta 0.4 )(C 0.89 N 0.11 ) has a lattice constant of 4.5551 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0158] Fig.65 Scanning electron microscopy (SEM) showed that (Hf 0.6 Ta 0.4 )(C 0.89 N 0.11 )Microstructure of solid solution powder. Fig.65 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.65(b) reveals that the side lengths of most cuboid particles are between 2 and 8 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1900℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.66 The particle size distribution is shown; it shows a skewed distribution trend, with the distribution peak mainly concentrated at 8 microns, accounting for about 25%. The average particle size is 3.81 microns.

[0159] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.67 As shown. The analysis results show that these particles contain four elements: Hf, Ta, C and N. Among them, the molar ratio of Hf to Ta is 1:0.69, which is consistent with the pre-designed ratio. The above data can confirm the successful preparation of (Hf 0.6 Ta 0.4 )(C 0.89 N 0.11 ) solid solution. Embodiment 19

[0160] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:0.25 respectively and mixing them evenly; (2) weighing cobalt powder at a mass ratio of 3:7 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating it to 1900°C at a heating rate of 2°C / min, keeping it at this temperature for 0.5 hour, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder was placed in an oven and dried at 60°C to obtain (Hf 0.8 Ta 0.2 )(C 0.89 N 0.11 ) micron powder.

[0161] The prepared transition metal carbonitride solid solution powder was subjected to X-ray diffraction (XRD) phase analysis, and the obtained XRD spectrum was as follows: Fig.68 Shown: In the 2θ range 30 o Up to 80 oThe five obvious XRD diffraction peaks detected correspond to the (111), (200), (220), (311) and (222) crystal planes of cubic carbonitride. The position of these diffraction peaks was used to calculate (Hf 0.8 Ta 0.2 )(C 0.89 N 0.11 ) has a lattice constant of 4.5895 Å, which is between the lattice constants of pure HfC (4.640 Å), TaC (4.450 Å), TaN (4.340 Å), and HfN (4.533 Å), indicating that a (Hf,Ta)(C,N) solid solution has been successfully formed.

[0162] Fig.69 Scanning electron microscopy (SEM) showed that (Hf 0.6 Ta 0.4 )(C 0.89 N 0.11 )Microstructure of solid solution powder. Fig.69 (a) shows that the particles have a rectangular morphology with sharp edges and a smooth surface; Fig.69 (b) reveals that the side lengths of most cuboid particles are between 2 and 14 μm. The original HfC and TaC raw materials have irregular powder morphology, but under the action of Co flux and after high temperature heat treatment at 1900℃, the solid solution particle morphology is transformed into a regular cuboid morphology. Fig.70 The particle size distribution is shown; it shows a skewed distribution trend, with the distribution peak mainly concentrated at 3 microns, accounting for about 20%. The average particle size is 3.46 microns.

[0163] The elemental composition and relative atomic percentage of the prepared cuboid microparticles were analyzed using an energy dispersive spectrometer (EDS) equipped on a scanning electron microscope, as shown in Fig.71 As shown. The analysis results show that these particles contain four elements: Hf, Ta, C and N. Among them, the molar ratio of Hf to Ta is 1:0.25, which is consistent with the pre-designed ratio. The above data can confirm the successful preparation of (Hf 0.8 Ta 0.2 )(C 0.89 N 0.11 ) solid solution. Embodiment 20

[0164] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:9 respectively and mixing them evenly; (2) weighing cobalt powder in a mass ratio of 1:1 between carbide and cobalt powder, and mixing them evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating to 1600°C at a heating rate of 5°C / min, keeping the temperature for 5 hours, and then cooling to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder is placed in an oven and dried at 50°C to obtain (Hf, Ta) (C, N) micron powder. Embodiment 21

[0165] The invention uses metal cobalt powder, hafnium carbide (HfC) powder and tantalum carbide (TaC) powder as raw materials, and the specific steps are as follows: (1) weighing hafnium carbide powder and tantalum carbide powder at a molar ratio of 1:0.11 respectively and mixing them evenly; (2) weighing cobalt powder at a mass ratio of 1:5 and mixing it evenly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and then transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere, heating to 1900°C at a heating rate of 2°C / min, keeping the temperature for 1 hour, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, and then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder is placed in an oven and dried at 80°C to obtain (Hf, Ta)(C, N) micron powder.

[0166] 2. Performance Test

[0167] Vickers hardness test

[0168] The (Hf,Ta)(C,N) / Co-based metal composite blocks obtained by high temperature heat treatment were embedded in resin to ensure the stability of the sample during the hardness test. They were then polished to 1 µm according to the standard metallographic polishing process.

[0169] The prepared metal / ceramic block was mounted with resin and then polished to 1 µm according to the standard metallographic polishing process. After polishing, the sample was thoroughly cleaned with soapy water to remove the polishing agent and other impurities on the surface, and then washed with deionized water and dried to ensure that the sample was clean and dry.

[0170] The hardness test was conducted using a micro Vickers hardness tester, and the test standard followed GB / T 4340 (1.2). The test conditions were set as follows: the load was 0.025 kg and the pressure was maintained for 10 seconds. When conducting the test, special attention should be paid to ensure that the indenter is accurately located at the center of the (Hf, Ta) (C, N) micron cuboid cross section to obtain accurate hardness performance. To ensure the reliability and repeatability of the results, at least 15 (Hf, Ta) (C, N) particles need to be tested for each sample. The Vickers hardness value, and the average value of these measurement points is calculated as the final hardness result.

[0171] Where Hf(C 0.89 N 0.11 ) has a Vickers hardness of 17.67±2.38 GPa, while Ta(C 0.89 N 0.11 ) has a Vickers hardness of 27.71±5.81 GPa. The properties of the products prepared in Examples 15 to 19 are summarized in Table 1. As can be seen from the table, the hardness properties of the formed (Hf, Ta)(C, N) solid solutions are higher than those of Hf(C, N) and Ta(C, N). In particular, the (Hf 0.6 Ta 0.4 )(C 0.89 N 0.11 ) solid solution micron-cubic particles showed the highest hardness value, reaching 47.81±5.05 GPa. 0.89 N 0.11 ) and Ta(C 0.89 N 0.11 ) hardness value, according to the linear law prediction, (Hf 0.6 Ta 0.4 )(C 0.89 N 0.11 ) sample should have an estimated hardness of 21.69 GPa. However, the actual hardness of the sample tested was 2.2 times higher than the value predicted by the linear law. This finding suggests that the formation of a (Hf, Ta)(C, N) solid solution is beneficial for significantly improving mechanical properties.

[0172] Table 1 Parameters and properties of the products prepared in each example Example Chemical formula Hf:Ta (molar ratio) Lattice constant (Å) Average particle size (µm) Hardness(GPa) 15 <![CDATA[(Hf 0.2 Are 0.8 )(C 0.89 N 0.11 )]]> 9:1 4.4820 7.50 31.34±4.34 16 <![CDATA[(Hf 0.4 Are 0.6 )(C 0.89 N 0.11 )]]> 4:1 4.5216 16.25 40.39±4.76 17 <![CDATA[(Hf 0.5 Are 0.5 )(C 0.89 N 0.11 )]]> 7:3 4.5391 6.99 42.31±6.02 18 <![CDATA[(Hf 0.6 Are 0.4 )(C 0.89 N 0.11 )]]> 3:2 4.5551 3.81 47.81±5.05 19 <![CDATA[(Hf 0.8 Are 0.2 )(C 0.89 N 0.11 )]]> 1:1 4.5895 3.46 35.11±5.57

Claims

1. A single-phase (Hf, Ta) (C, N) transition metal carbonitride powder, a preparation method and use thereof, characterized in that: The method comprises the following steps: (1) weighing hafnium carbide powder and tantalum carbide powder in a molar ratio of 1:(0.11-9) and mixing them uniformly; (2) weighing cobalt powder in a mass ratio of 1:(1-5) and mixing them uniformly with the powder obtained in step (1); (3) pressing the mixed powder obtained in step (2) into a prefabricated block and transferring it to a high-temperature furnace for heat treatment in a nitrogen atmosphere at a heating rate of 2-5°C / min to 1500°C-1900°C, keeping the temperature for 0.5-10 hours, and then cooling it to room temperature with the furnace to generate a (Hf, Ta)(C, N) / Co-based metal ceramic block; and (4) immersing the product in a nitric acid solution to dissolve the cobalt-rich alloy matrix by corrosion, then filtering the remaining powder, and repeatedly washing it with deionized water to remove impurities and ions on the surface of the powder. (5) The cleaned powder is placed in an oven and dried at 50°C to 80°C to obtain (Hf, Ta) (C, N) micron powder.

Citation Information

Patent Citations

  • Controllable niobium carbide-tantalum carbide solid solution micron cube and preparation method thereof

    CN112374892A

  • Synthesis method of (TiZrHfNbTa) CN high-entropy ultrahigh-temperature carbonitride ceramic powder

    CN114315370A

  • Preparation method of titanium niobium tantalum carbide continuous solid solution

    CN115536395A

  • Preparation method of hafnium tantalate powder

    CN118877938A

  • Multicomponent carbonitride powder, manufacturing method therefor, and sintered compact by using it as raw material

    JP2003013102A